Droop based Demand Dispatch for Residential Loads in Smart Grid Application - Ashourpouri, A.; Ghosh, Arindam; Rajakaruna, Sumedha (Walter de Gruyter GmbH, 2018)
Aggregated loads play a significant role in maintaining the frequency of power system when the generation is not able to follow frequency deviations. An automatic Demand Dispatch (DD) enables the power system to employ the aggregated loads for balancing demand and supply. In this paper, a Demand Side Frequency Droop (DSFD) has been proposed which provides ancillary service to the grid and maintains the frequency of the power system when the generation system is not capable of following the demand. At the time of a frequency fall/rise, Balancing Authority (BA) can detect aggregated load or group of aggregated loads that have power consumption above or below their standard maximum/minimum consumption levels. Then, the BA issues a droop-based signal to the relevant aggregator. Afterwards, the DSFD will be implemented in the aggregator or the group of aggregators to specify the required power consumption amount for bringing the frequency back to its rated level. Subsequently, this signal will be sent to the Appliance Management Unit (AMU) at each participating house. The AMU sends the signal in the form of deferral or interruptible commands to the appliances depending on the priority, availability and the specification of the appliances. It will be demonstrated that the proposed DSFD control maintains the frequency of the power system within a specified range.